What factors influence dyadic synchrony? A systematic review of the literature on predictors of mother–infant dyadic processes of shared behavior and affect. Issue 5 (1st August 2022) - Golds, Lisa; Gillespie‐Smith, Karri; Nimbley, Emy; MacBeth, Angus
Abstract: Dyadic behavioral synchrony is a complex interactional process that takes place between the mother and her infant. In the first year of life, when the infant is prelinguistic, processes such as synchrony enable the dyad to communicate through shared behavior and affect. To date, no systematic review has been carried out to understand the risk and protective factors that influence behavioral synchrony in the mother–infant dyad. The aim of this review was to identify and evaluate the factors that influence behavioral synchrony in the mother–infant dyad, when the infant is between 3 and 9 months old. Key electronic databases were searched between 1970 and April 2021, and 28 eligible studies were identified for review. As the results were largely heterogeneous, four subgroups of factors were identified: (i) infant demographics, (ii) physiological factors, (iii) maternal mental health, and (iv) miscellaneous factors. Identified risk factors and covariates suggest that social determinants of health, underpinned by biological factors, play a large role in influencing behavioral synchrony within the dyad. Implications for the need to identify additional risk and protective factors, as well as design support for at‐risk families are discussed. Resumen: La sincronía diádica del comportamiento es un proceso complejo de interacción que se lleva a cabo entre la madre y su infante, y en el primero año de vida, cuando el infante está en la época prelingüística. Los procesos como la sincronía le permiten a la díada comunicarse a través del comportamiento y el afecto compartido. Hasta la fecha, ninguna revisión sistemática se ha llevado a cabo para comprender los factores de riesgo y de protección que influyen la sincronía del comportamiento en la díada madre‐infante. El propósito de esta revisión fue identificar y evaluar los factores que influyen la sincronía del comportamiento en la díada madre‐infante, cuando el infante tiene entre 3 y 9 meses de nacido. Se investigaron bancos claves de datos electrónicos entre 1970 y abril de 2021, y se identificaron 28 estudios aptos para la revisión. Como los resultados fueron en gran parte heterogéneos, se identificaron cuatro subgrupos de factores: (i) datos demográficos del infante, (ii) factores fisiológicos, (iii) salud mental materna, y (iv) factores misceláneos. Los factores de riesgo y covariantes identificados señalan que los determinantes sociales de salud, sustentados por factores biológicos, juegan un papel grande en cuanto a influir la sincronía del comportamiento dentro de la díada. Se discuten las implicaciones para la necesidad de identificar factores de riesgo y de protección adicionales, así como también diseñar el apoyo para familias bajo riesgo. Résumé: La synchronie comportementale dyadique est un processus interactionnel complexe qui prend place entre la mère et son bébé. Dans la première année de la vie, quand le bébé ne parle pas, les processus tels que la synchronie permettent à la dyade de communiquer à travers un comportement et un affect partagés. Jusqu'à présent aucune revue systématique n'a été faite pour comprendre les facteurs de risque et les facteurs de protection qui influencent la synchronie comportementale chez la dyade mère‐bébé. Le but de cette revue était d'identifier et d'évaluer les facteurs qui influencent la synchronie comportementale chez la dyade mère‐bébé, quand le bébé avait entre 3–9 mois. Les bases de données électroniques clés ont fait l'objet des recherches entre 1970 et avril 2021, et 28 études admissibles ont été identifiée pour la revue. Puisque les résultats étaient largement hétérogènes, quatre sous‐groupes de facteurs ont été identifiés: (1) données démographiques du bébé, (ii) facteurs physiologiques, (iii) santé mentale maternelle, et (iv) facteurs divers. Les facteurs de risque identifiés et les co‐variables suggèrent que les déterminants sociaux de la santé, sous‐tendus par des facteurs biologiques, jouent un rôle important en influençant la synchronie comportementale au sein de la dyade. Les implications quant au besoin d'identifier des facteurs de risque et de protection supplémentaire, ainsi que des soutiens aux familles à risque sont discutées. Zusammenfassung: Welche Faktoren beeinflussen dyadische Synchronität? Ein systematischer Reviewartikel zu den Prädiktoren dyadischer Mutter‐Kind‐Prozesse bezogen auf gemeinsames Verhalten und gemeinsamen Affekt Dyadische Verhaltenssynchronität ist ein komplexer Interaktionsprozess, der zwischen einer Mutter und ihrem Säugling abläuft. Im ersten Lebensjahr, wenn der Säugling noch nicht sprachfähig ist, ermöglichen Prozesse wie die Synchronität durch gemeinsames Verhalten und gemeinsamen Affekt die Kommunikation innerhalb der Dyade. Bislang wurde noch keine systematische Untersuchung durchgeführt, um die Risiko‐ und Schutzfaktoren zu verstehen, die Verhaltenssynchronität in der Mutter‐Kind‐Dyade beeinflussen. Ziel dieses Reviewartikels war es, Faktoren zu ermitteln und auszuwerten, die Verhaltenssynchronität in der Mutter‐Kind‐Dyade beeinflussen, wenn der Säugling zwischen 3 und 9 Monate alt ist. Zwischen 1970 und April 2021 wurden die wichtigsten elektronischen Datenbanken durchsucht und es wurden 28 in Frage kommende Studien für das Review ausgewählt. Da die Ergebnisse weitgehend heterogen waren, wurden bezüglich der Faktoren vier Untergruppen ermittelt: (i) demografische Faktoren des Säuglings, (ii) physiologische Faktoren, (iii) psychische Gesundheit der Mutter und (iv) sonstige Faktoren. Die identifizierten Risikofaktoren und Kovariaten deuten darauf hin, dass soziale Gesundheitsfaktoren, gestützt durch biologische Faktoren, eine große Rolle bei der Beeinflussung der Verhaltenssynchronität innerhalb der Dyade spielen. Implikationen für die Notwendigkeit, zusätzliche Risiko‐ und Schutzfaktoren zu identifizieren und Unterstützungskonzepte für gefährdete Familien zu entwickeln, werden diskutiert. 抄録: 二者同調性に影響を与える要因は何か？ 母親‐乳児二者の共有された行動と情動のプロセス予測因子に関する文献の系統的レビュー 二者の行動同調性は、母親とその乳児との間で起こる複雑な相互交流プロセスである。乳児が前言語的である生後1年間においては、同調のようなプロセスが、行動と感情の共有による二者のコミュニケーションを可能にする。これまで、母親‐乳児の二者の行動同調性に影響を与える危険因子と保護因子を理解することを目的とした、系統的レビューは実施されていない。このレビューの目的は、生後3～9ヶ月の乳児の母‐乳児間の行動の同調性に影響を与える因子を特定し、評価することであった。1970年から2021年4月の主要な電子データベースを検索し、28件の適格な研究を確定し、レビューを行った。結果は広く多様な要因に渡ったため、4つのサブグループの要因を特定した。(i)乳児の人口統計学、(ii)生理学的要因、(iii)母親の精神衛生、(iv)その他様々な要因。特定されたリスク因子と共変量は、生物学的因子に裏づけされた健康の社会的決定要因が、二者間の行動同調性に大きな影響を与えることを示唆している。さらに、他のリスク因子と保護因子を明らかにし、リスクのある家族への支援を計画する必要性について論じた。 摘要: 二元行为同步是发生在母亲和婴儿之间的一个复杂的互动过程, 在婴儿出生后的第一年, 当婴儿还没有学会语言时, 诸如同步这样的过程使母婴之间能够通过共同的行为和情感进行交流。迄今为止, 还没有系统的研究来了解影响母婴行为同步的风险和保护因素。本综述的目的是确定和评估在婴儿3至9个月大时影响母婴行为同步的因素。检索了1970年至2021年4月期间的主要电子数据库, 确定了28项符合条件的研究开展综述。由于结果在很大程度上是不同的, 因此确定了四个分组因素: (一) 婴儿人口统计数据; (二) 生理因素; (三) 母亲心理健康; (四) 杂项因素。已确定的风险因素和协变量表明, 以生物因素为基础的健康的社会决定因素在影响二元组内的行为同步方面发挥着重要作用。本综述还讨论了识别其他风险和保护因素的必要性, 以及开展高危家庭支持的作用。 ملخص: ما هي العوامل التي تؤثر على التزامن الثنائي؟ مراجعة منهجية للأدبيات المتعلقة بالتنبؤ بالعمليات الثنائية بين الأم والرضيع للسلوك والعاطفة المشتركة التزامن السلوكي الثنائي هو عملية تفاعلية معقدة تحدث بين الأم وطفلها ، وفي السنة الأولى من الحياة ، عندما يكون الرضيع في المرحلة قبل اللغوية ، فإن عمليات مثل التزامن تمكن الثنائي من التواصل من خلال السلوك المشترك والعاطفة. حتى الآن ، لم يتم إجراء مراجعة منهجية لفهم عوامل الخطر والحماية التي تؤثر على التزامن السلوكي في ثنائي الأم والرضيع. كان الهدف من هذه المراجعة هو تحديد وتقييم العوامل التي تؤثر على التزامن السلوكي في ثنائيات الأم والرضيع ، عندما يكون الرضيع بين 3 ‐ 9 أشهر من العمر. تم البحث في قواعد البيانات الإلكترونية الرئيسية بين 1970 وحتى إبريل 2021 ، وتم تحديد 28 دراسة مؤهلة للمراجعة. نظرًا لأن النتائج كانت غير متجانسة إلى حد كبير ، تم تحديد أربع مجموعات فرعية من العوامل: (1) التركيبة السكانية للرضع ، (2) العوامل الفسيولوجية ، (3) الصحة النفسية للأم ، و (4) العوامل المتنوعة. تشير عوامل الخطر والمتغيرات المشتركة التي تم تحديدها إلى أن المحددات الاجتماعية للصحة ، المدعومة بعوامل بيولوجية ، تلعب دورًا كبيرًا في التأثير على التزامن السلوكي في الثنائي. تمت مناقشة التطبيقات المترتبة على الحاجة إلى تحديد عوامل الخطر والحماية الإضافية ، فضلاً عن دعم التصميم للأسر المعرضة للخطر